A Novel Homozygous MYO7A Mutation: Case Report - Mahsa Ahmadi; Ali Dehghanifard; Alireza Isazadeh; Saba Hajazimian; Mahshad Mehdizadeh; Shiva Rahaei; Soudabeh Hosseini; Ebrahim Kalantari (Acta Medica Iranica, 2018)
MYO7A is an unconventional myosin that is essential for ordinary hearing and vision; mutations in the MYO7A gene result in Usher syndrome type 1B and other disorders. In this manuscript, we reported a mutation (c.4705delA) in exon 35, causing the alteration of a Ser amino acid to Ala at codon 1569 (p.H2027del) located within the first FERMdomain of the human protein myosin VIIA. This mutation involved in the pathogenesis of hearing loss, congenital night blindness, muscular weakness, skin problem, and difficulty in keeping balance in the 13-year-old female. After checkup the patient’s DNA was extracted from peripheral blood and amplification was performed by PCR. Sequencing method was performed for identification of the mutation. The c.4705delA mutation in exon 35 was found in the patient in heterozygosis form; this means that her mother and father were carriers. This mutation is located on the tail of the myosinVIIA protein and is associated with several disorders.